2013
DOI: 10.1038/ng.2564
|View full text |Cite
|
Sign up to set email alerts
|

GWAS meta-analysis and replication identifies three new susceptibility loci for ovarian cancer

Abstract: Genome wide association studies (GWAS) have identified four susceptibility loci for epithelial ovarian cancer (EOC) with another two loci being close to genome-wide significance. We pooled data from a GWAS conducted in North America with another GWAS from the United Kingdom. We selected the top 24,551 SNPs for inclusion on the iCOGS custom genotyping array. Follow-up genotyping was carried out in 18,174 cases and 26,134 controls from 43 studies from the Ovarian Cancer Association Consortium. We validated the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
380
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 340 publications
(395 citation statements)
references
References 40 publications
5
380
2
7
Order By: Relevance
“…We found that 104 SNPs were significantly associated with cancer risk among 594 patients with serous ovarian cancers and 1,172 controls (P meta o1.00 Â 10 À 4 ). Of these 104 SNPs, 21 SNPs were also significantly associated with overall risk of ovarian cancer, and rs6784988 (P serous ¼ 3.57 Â 10 À 7 ; P total ¼ 2.23 Â 10 À 6 ) at 3q26.33 and rs7420064 (P serous ¼ 3.87 Â 10 À 7 ; P total ¼ 4.04 Â 10 À 6 ) [12][13][14][15][16][17] . The present study in Han Chinese populations also tested the risk associations with the 11 previously reported SNPs from those GWAS analyses, but only 8 SNPs were included in our GWA scan or imputation analyses, of which four SNPs (rs2665390 at 3q25, rs9303542 at 17q21, rs8170 at 19p13.11 and rs757210 at 17q12) were found to be significantly associated with EOC risk in our stage I study.…”
Section: Association Analyses We Conduct a Three-stage Gwas In Hanmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 104 SNPs were significantly associated with cancer risk among 594 patients with serous ovarian cancers and 1,172 controls (P meta o1.00 Â 10 À 4 ). Of these 104 SNPs, 21 SNPs were also significantly associated with overall risk of ovarian cancer, and rs6784988 (P serous ¼ 3.57 Â 10 À 7 ; P total ¼ 2.23 Â 10 À 6 ) at 3q26.33 and rs7420064 (P serous ¼ 3.87 Â 10 À 7 ; P total ¼ 4.04 Â 10 À 6 ) [12][13][14][15][16][17] . The present study in Han Chinese populations also tested the risk associations with the 11 previously reported SNPs from those GWAS analyses, but only 8 SNPs were included in our GWA scan or imputation analyses, of which four SNPs (rs2665390 at 3q25, rs9303542 at 17q21, rs8170 at 19p13.11 and rs757210 at 17q12) were found to be significantly associated with EOC risk in our stage I study.…”
Section: Association Analyses We Conduct a Three-stage Gwas In Hanmentioning
confidence: 99%
“…Molecular epidemiological studies have been conducted with the candidate gene approach to identify low penetrance susceptibility genes for ovarian cancer, many of which have showed inconsistent results [4][5][6][7][8][9][10][11] . Recent genome-wide association studies (GWASs) have reported 11 new singlenucleotide polymorphisms (SNPs) that are associated with ovarian cancer risk in European populations [12][13][14][15][16][17] . However, the results from the published GWASs have also demonstrated race-and ethnicity-specific cancer susceptibility 18 .…”
mentioning
confidence: 99%
“…Recent advances in our understanding of disease pathogenesis across many fields of medicine, such as the shift from classification of cancer by organ system to the tumor's molecular signature, 62,63 diverse immunologic conditions/diseases resulting from shared pathogenic influences, 64 and the strong link between CNS disorders and the gut microbiota, 65 have revealed the importance of dismantling boundaries between medical specialties. Likewise, emerging evidence from genetics and neuroscience has implicated common environmental/ pathogenetic factors (eg, neurodevelopmental, immunologic, and infectious) and genes underlying schizophrenia, 43,66,67 autism, 49,68 and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Participants from 43 studies from around the world were genotyped using the Illumina Infinium iSelect (iCOGS) array. 23 Quality control was as per previous work, with related individuals and ancestry outliers removed. 4 We excluded 13 studies of individuals of nonEuropean ancestry 4 ; the remaining studies that contributed to our analysis are listed in Supplementary Table 4 (available as Supplementary data at IJE online).…”
Section: Data Sourcesmentioning
confidence: 99%